Comparison of the Effectiveness of Providing Spiritual Emotional Freedom Technique (SEFT) Therapy with Therapy 3HZ Frequency on Improving Sleep Quality Teenagers Who Experience Insomnia at Papua Pegunungan Junior High School in 2024 - Abela Mayunita; Isticharoh Isticharoh; Risti Septiani; Erlina Hasiholan; Kiki Amalia (Jurnal Penelitian Pendidikan IPA, 2025)
Insomnia among adolescents in Papua Mountains is increasingly prevalent and negatively affects cognitive performance and emotional well-being. This study aimed to compare the effectiveness of Spiritual Emotional Freedom Technique (SEFT) therapy and 3 Hz frequency therapy in improving sleep quality among junior high school students with insomnia in 2024. A quasi-experimental study with a Non-Equivalent Control Group Design was conducted on 101 respondents selected through purposive sampling from three schools: Usilimo State Junior High School (n=35), Yapis Wamena Junior High School (n=33), and Sogokmo Adventist Junior High School (n=33). Data were analyzed using the Wilcoxon signed-rank test. Results showed that SEFT therapy improved sleep quality with significant effects at Usilimo (p=0.003) and Yapis Wamena (p=0.025), but not at Sogokmo Adventist (p=0.083). In contrast, 3 Hz frequency therapy consistently demonstrated highly significant improvements across all schools (p<0.001). In conclusion, 3 Hz frequency therapy is more effective than SEFT therapy in improving sleep quality among adolescents with insomnia in Papua Mountains.